BAGAIMANA PERAN DAN PENERAPAN AKUNTANSI HIJAU DI INDONESIA? - Yasrawan, Komang Tri; Werastuti, Desak Nyoman Sri (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. The purpose of this study was to determine the role of green accounting in reducing environmental pollution and to examine the extent to which the application of green accounting in Indonesia supported sustainability.Research Method. This study used an interpretive approach that focused on the subjective nature of the social world and tried to understand it.Research Result and Findings. Reporting environmental costs in green accounting will certainly help stakeholders to evaluate environmental conservation and improve environmental management efficiency to support business continuity in the present and in the future. Green accounting had difficulty in measuring the value of costs and benefits of externalities arising from industrial processes. It was not easy to measure the harm that occurs to the people around and the ecological environment caused by air pollution, liquid waste, ammonia tube leaks, nuclear tube leaks, or other externalities. Unfortunately, in practice, often some companies did not report the bad news they face, so reporting environmental costs was not effective.